CASE OF IATROGENIC CUSHING'S SYNDROME BY TOPICAL TRIAMCINOLONE - Zil-E-Ali, Ahsan; Janjua, Omer Hanif; Latif, Aiza; Aadil, Muhammad (Journal of Ayub Medical College Abbottabad, 2018)
Cushing's syndrome is a collection of signs and symptoms due to hypercortisolism. Prolong use of topical steroid may cause this syndrome and suppression of hypothalamic and pituitary function, however such events are more common with oral and parenteral route. There are very few cases of Cushing's syndrome with a topical application amongst which triamcinolone is the rarest drug. We report a case of 11-year-old boy is presented who developed Cushing's disease by topical application. The child had body rashes for which the caregiver consulted a local quack, a topical cream of triamcinolone was prescribed. After application for three months, the patient became obese and developed a moon-like face. A thorough biochemical workup and diagnostic test for Cushing's disease was done to confirm. The following case report a dramatic example of development of the syndrome from chronic topical application of the least potent corticosteroid Keywords: Triamcinolone; Cushing Syndrome; Endocrinology